The Adaptation Strategy of Flash Flood Victims in Urban Areas, Garut Kota Sub-District - Ulfa Azhari Shabira; Sri Rum Giyarsih (Forum Geografi, 2021)
In 2016, various settlements in Garut Regency, notably Garut Kota Sub-District, located along the Cimanuk River, were affected by a flash flood. As a result, many residents relocated to other places, far from the city. This research was conducted in three residential relocation areas: Gadok Housing, Kopi Lombang Housing and Cisereuh Housing. The purpose of the study is to determine the adaptation strategies of relocating communities. The research was conducted using mixed-methods techniques with descriptive quantitative and qualitative data analysis. The results are shown in the adaptation strategies of the affected communities and demonstrate that the relocated communities living in new settlements pursued adaptation strategies such as adjustment and adaptation with reaction. Adaptation by adjustment was carried out by accepting the post-relocation situation and taking up jobs in different sectors. Meanwhile, adaptation by reaction entailed making changes to the physical form of buildings, planting mixed gardens or constructing pet cages in the yard. Relocating residents often lacked the motivation to move to alternative shelters due to financial inability and a sense of comfort in their new settlement.